2021
DOI: 10.1002/adfm.202107599
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Nature of Nanohydroxyapatite in Tumor Progression

Abstract: Nanohydroxyapatite (nHAP) has broad applications because of its nanoscopical dimension, large specific surface area, biocompatibility, and low cytotoxicity. Researchers recently discovered that nHAP synthesized in vitro inhibits the growth of different types of tumor cells. Nanohydroxyapatite with potent drug adsorption and loading capacity has potential applications in tumor diagnosis and treatment. Because local tumors and areas of tumor metastasis also produce pathological nHAP in vivo to promote progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 216 publications
(266 reference statements)
0
9
0
Order By: Relevance
“…Chloroquine may also be loaded in biodegradable scaffolds for sustained release in the biliary or urinary tract to reduce the risk of calculus recurrence. It is worth noting that the abnormal "charge pool" may be related to other diseases such as cancer and atherosclerosis [49][50][51] . The present strategy may pave the way for development of inspirational treatment for diseases like cancer and atherosclerosis based on the principle of "charge pool" adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine may also be loaded in biodegradable scaffolds for sustained release in the biliary or urinary tract to reduce the risk of calculus recurrence. It is worth noting that the abnormal "charge pool" may be related to other diseases such as cancer and atherosclerosis [49][50][51] . The present strategy may pave the way for development of inspirational treatment for diseases like cancer and atherosclerosis based on the principle of "charge pool" adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that nHAp can reduce telomerase levels in tumor cells (Motskin et al, 2009). Treatment of tumor cells with nHAp at varying concentrations has shown that telomerase activity decreases as nHAp concentration increases, while the apoptosis rate increases with higher nHAp content (He et al, 2022).…”
Section: Inhibits Telomerase Activitymentioning
confidence: 99%
“…HAP at nanoscales present peculiar properties, such as reactivate surface, mechanical properties, electrochemical properties [4]. It is strong surface energy and positive charge of nano-HAP enable them attach to the negative charge surface of tumor cells, preventing tumor cells adhesion and proliferation [5]. Nano-HAP has been used as an adsorbent due to the high surface area and surface functional groups (both positively charged Ca 2+ and negatively charged PO4 3-ions) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nano-HAP can influence the tensile strength of gel composites by mixing different nano-HAP content [7]. In particular, in the review of He et al , association between physical properties of nano-HAP and tumor cell response are accurately described [5]. Thus, different from conventional micro-sized HAP, nano-HAP can be served as regenerative medicine, anti-tumor agents [8], efficient drug delivery cargos [2], few environmental applications [6].…”
Section: Introductionmentioning
confidence: 99%